Gliadel use in a pregnant patient with malignant glioma: a case report - Venkitasubramony, Vishnu; Tahbaz, Meghan; Huang, Kian A.; Cain, Mary A.; Preuss, Charles; Tran, Nam D. (Frontiers in Oncology, 2025)
Malignant gliomas during pregnancy represent a rare and complex clinical challenge, with limited data to guide management. We report a case of a 35-year-old woman with World Health Organization (WHO) grade III anaplastic astrocytoma who presents at 18 weeks’ pregnancy with progressive disease. She underwent craniotomy for tumor resection with implantation of intralesional carmustine (Gliadel) wafers. Histopathology confirmed progression to WHO grade IV astrocytoma. The patient remained neurologically stable and delivered a healthy infant by cesarean section at 26 weeks’ gestation. Postpartum, she initiated systemic therapy but ultimately experienced progression and died 4 months later. Her daughter remains healthy with normal development more than 14 years after birth. Carmustine use during pregnancy is rarely reported and intralesional carmustine use in pregnancy has never been reported. Pharmacokinetics suggests minimal systemic absorption, limiting fetal exposure. Our case adds to the limited literature, highlighting the feasibility of local chemotherapy with carmustine wafers during the second trimester.